Productive and monetary efficiency of radish and coriander intercropping under organic management - Gerlani Alves Silva; Francisco Bezerra Neto; Jailma Suerda Silva de Lima; Elizangela Cabral dos Santos; Vitor Abel da Silva Lino; Francisca Karla Kelly da Silva Lino; Jéssica Paloma Pinheiro da Silva; Erivan Alves da Silva (Revista Ciência Agronômica)
ABSTRACT The search for cropping systems that aim to have the best area use, optimize production, and guarantee financial profitability to the producer and their establishment in the field are challenges of modern research. Thus, the objective of this study was to evaluate the productive and monetary viability of intercropping radish and coriander fertilized with equitable amounts of hairy woodrose and roostertree biomass from the Caatinga ecosystem at different coriander population densities in two cropping seasons. The experimental design used was randomized blocks, with treatments arranged in a 4 × 4 factorial scheme with four replications. The first factor was constituted by four equitable amounts of hairy woodrose and roostertree biomass (20, 35, 50 and 65 t ha-1 on a dry basis), and the second factor was constituted by coriander population densities (40, 60, 80 and 100% of the recommended density for monocropping, RDM). The greatest agronomic and monetary advantages of intercropping radish with coriander were obtained with a land equivalent coefficient and a monetary equivalence ratio of 0.42 and 0.76, respectively, in the amounts of hairy woodrose and roostertree biomass of 20 and 39 t ha-1 added to the soil, in the coriander population density of 100% of the RDM. The coriander green mass yield and commercial productivity of radish roots optimized in the intercropping were 1.25 and 14.90 t ha-1 when fertilized with 65 t ha-1 of green manures biomass in the coriander population density of 100% RDM.